Outbreak of Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis Associated With Mebendazole and Metronidazole Use Among Filipino Laborers in Taiwan - Chen, Kow-Tong (© American Journal of Public Health 2003, 2003)
Objectives. This study sought to identify the risk factors associated with an outbreak of Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) among Filipino laborers in Taiwan. Methods. Forty-six SJS/TEN patients were matched to 92 controls according to month of arrival in Taiwan, sex, and age. Results. The odds ratio for development of SJS/TEN was 9.5 (95% confidence interval [CI] = 3.9, 23.9) among workers who had used both metronidazole and mebendazole sometime in the preceding 6 weeks. In addition, a gradient increase in the occurrence of SJS/TEN was found with an increasing level of exposure to metronidazole. Conclusions. This outbreak highlights the risk of SJS/TEN resulting from the use of both metronidazole and mebendazole and the need for control measures.